PENGEMBANGAN BAHAN AJAR BERBANTUAN MICROSOFT SWAY UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DALAM PEMBELAJARAN DARING - Barita Riana Sitours; Ahmad Yani T; Yundari Yundari; Zubaidah Zubaidah; Hamdani Hamdani (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
The ability to understand concepts and critical thinking skills of students in Indonesia is still relatively low and teaching materials play an important role in the learning process. This development research aims to produce teaching materials with Microsoft Sway that contain line and angle material, that was feasible to implement and effective for increasing students' conceptual understanding and critical thinking skills in online learning. The development of teaching materials is carried out by following the ADDIE method, namely analysis, design, development, implementation and evaluation. The teaching materials that have been developed are then validated by 2 media experts and 2 material experts. Teaching materials that have been validated are then tested individually (3 students) and tested on a limited group (30 students). The data in this study were obtained from response questionnaires and the results of the students' pre-test and post-test. This study produced teaching materials with Microsoft Sway that contain line and angle materials which were tested to be very feasible to implement with an average feasibility test score by material experts of 3.76 and an average feasibility score by media experts of 3.63. In addition, teaching materials with Microsoft Sway are also effective for increasing students' conceptual understanding and critical thinking skills, as evidenced by the gain score obtained based on the results of the pre-test and post-test of 0.67 which is included in the medium category and classically 86.67% of students get post-test scores that meet the minimum completeness criteria.